2023
DOI: 10.1002/ptr.8013
|View full text |Cite
|
Sign up to set email alerts
|

Galangin: A food‐derived flavonoid with therapeutic potential against a wide spectrum of diseases

Daibo Wang,
Junren Chen,
Lin Pu
et al.

Abstract: Galangin is an important flavonoid with natural activity, that is abundant in galangal and propolis. Currently, various biological activities of galangin have been disclosed, including anti‐inflammation, antibacterial effect, anti‐oxidative stress and aging, anti‐fibrosis, and antihypertensive effect. Based on the above bioactivities, more and more attention has been paid to the role of galangin in neurodegenerative diseases, rheumatoid arthritis, osteoarthritis, osteoporosis, skin diseases, and cancer. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 157 publications
0
0
0
Order By: Relevance
“…The effect of galangin on GC cell growth was also investigated in vivo by conducting a mouse study. A reduction in the ratio of p-JAK2/JAK2 (Janus-associated kinase) and p-STAT3/STAT3, protein expression of Bcl-2, CASP3, and Ki67 was demonstrated, while increased protein expression of cleaved CASP3 and cleaved PARP was observed [31,97]. A comparative study comparing the effects of galangin and quercetin on the SGC-7901 GC cell line showed greater efficacy of galangin, which inhibited cell growth, induced apoptosis, and reduced mitochondrial membrane potential (MMP).…”
Section: Galangalmentioning
confidence: 97%
See 4 more Smart Citations
“…The effect of galangin on GC cell growth was also investigated in vivo by conducting a mouse study. A reduction in the ratio of p-JAK2/JAK2 (Janus-associated kinase) and p-STAT3/STAT3, protein expression of Bcl-2, CASP3, and Ki67 was demonstrated, while increased protein expression of cleaved CASP3 and cleaved PARP was observed [31,97]. A comparative study comparing the effects of galangin and quercetin on the SGC-7901 GC cell line showed greater efficacy of galangin, which inhibited cell growth, induced apoptosis, and reduced mitochondrial membrane potential (MMP).…”
Section: Galangalmentioning
confidence: 97%
“…Galangin is a natural flavonoid compound [(3,5,7-trihydroxyflavone (C 15 H 10 O 5 )]. It exhibits anti-inflammatory, antimicrobial, antioxidant, antiviral, and apoptotic activities [30][31][32]. Research is being conducted on its use in the treatment of cancer, gastrointestinal diseases, diabetes, obesity, rheumatoid inflammation, arthritis, neuropathy, or osteoporosis [31,32].…”
Section: Galangalmentioning
confidence: 99%
See 3 more Smart Citations